Pädagogik, disciplinary institutionalization and dictatorships: on the history of a disciplinary field and its problems - Canales Serrano, Antonio Francisco (Historia y Memoria de la Educación, 2020)
This essay reflects on the questions posed by historical research regarding the institutionalization of educational sciences and Pädagogik, on the occasion of the publication of the book Education and «Pädagogik»: philosophical and historical reflections (Central, Southern and South-Eastern Europe), edited by Blanka Kudláčová and Andrej Rajský. In a first part, the essay deals with the problems of translating into English the concepts used to account for European continental cases and the dangers of misrepresenting their historical logic. A second part focuses on the discussion of the chapters of the book and defends the need to advance in a theoretical framework on the boundary between science and politics in the case of dictatorships and o allow for the experience of the former communist countries to be included.